Acute Presentation of an unblocked Phaeochromocytoma with Small Bowel Ischaemia managed by Emergency Laparotomy and Adrenalectomy. (1st March 2022) - Houghton, Neil; Davies, Brooke; Hansel, Jan; Davies, Douglas; Smith, Paul; Brown, Andrew; Perkins, Karen; Krishnaprasad, Karnad; Ryska, Ondrej; Walls, Gerard; Tomlinson, Mark
Abstract: Introduction: A 50-year-old male presented as an emergency with acute abdominal pain, reduced consciousness and blood pressure of 230/136mmHg, having felt unwell for a year. CT scans showed a 9cm right adrenal mass, a 27mm left ventricular thrombus and emboli to the distal superior mesenteric artery. Echocardiography demonstrated a reduced ejection fraction of 25%. Methods: Our regional multidisciplinary team (Endocrinologists, Anaesthetists, Intensivists, Biochemists and Surgeons) utilised their experience to manage this challenging emergency, with supra-regional expert consultation. Results: In ICU, intravenous phentolamine and unfractionated heparin infusions were given, attempting to avoid surgery until alpha blockade was established. The following day sepsis and peritonitis developed: surgery could no longer be deferred and had to be undertaken without blockade. After anaesthetic induction a 12 minute asystolic arrest ensued, but circulation was restored with CPR and bolus noradrenaline. Intraoperative photographs demonstrate 150cm of infarcted small bowel being resected, and sequential adrenalectomy being undertaken to avoid further catecholamine crisis and anaesthetic, as discussed with supra-regional colleagues. Post-arrest targeted temperature management was instigated alongside empirical steroid replacement. Serum metadrenaline fell from 58, 495pmol/L (<510pmol/L) to 174pmol/L and normetadrenaline from 78, 731pmol/L (<1180pmol/L) to 330pmol/L post-resection. Histological assessment confirmed phaeochromocytoma with malignant features (PASS=6 and GAPP=5). The patient made a full recovery and ejection fraction improved to 55%. Conclusion: This case adds to the controversial equipoise regarding pre-operative blockade. An experienced multidisciplinary adrenal team was crucial in managing this life threatening combination. Noradrenaline was effective during cardiac arrest whilst the circulation was unresponsive to adrenaline.